2013
DOI: 10.2741/4122
|View full text |Cite
|
Sign up to set email alerts
|

miR-143 is critical for the formation of primordial follicles in mice 

Abstract: Although microRNAs (miRNAs) have been implicated in fine-tuning gene networks, the roles of mmu-mir-143 (miR-143) in mammalian ovary development have not been studied in vitro. We investigated the expression and function of miR-143 in the mouse ovary during primordial follicle formation. Real-time polymerase chain reaction analysis showed that miR-143 expression increased during primordial follicle formation from 15.5 days post-coitus to 4 days post-partum. miR-143 was located in pregranulosa cells by in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Most recently, microRNA expression profiles have been established in ovaries in human (Zhang et al 2011), mice (Choi et al 2007, Ro et al 2007, Ahn et al 2010, Zhang et al 2013, and cattle (Tripurani et al 2010 around the time of primordial follicle assembly. All these studies suggested important roles of microRNAs in the developing ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, microRNA expression profiles have been established in ovaries in human (Zhang et al 2011), mice (Choi et al 2007, Ro et al 2007, Ahn et al 2010, Zhang et al 2013, and cattle (Tripurani et al 2010 around the time of primordial follicle assembly. All these studies suggested important roles of microRNAs in the developing ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics and Gene Ontology analysis revealed that the target genes of these predominantly expressed miRNAs in the ovary are involved in cell cycle regulation; cellular growth, proliferation and apoptosis; endocrine system disorders; and ovarian functions [ 29 ]. In addition, a recent study demonstrated that miR-143 inhibited primordial follicle formation by reducing the expression of cyclin-dependent kinases (CDKs) 4 and 6 and cyclins B1, D2, and E2 in pregranulosa cells [ 30 ]. Furthermore, miR-181a inhibits mouse ovarian granulosa cell proliferation by targeting activin receptor IIA [ 31 ], and miR-26b promotes ovarian granulosa cell apoptosis by targeting the ataxia telangiectasia mutated (ATM) gene during follicular atresia [ 32 ].…”
Section: Mirna Profiles In the Ovarymentioning
confidence: 99%
“…Zhang et al revealed that miR-143 was expressed in pregranulosa cells using in situ hybridization. miR-143 inhibits the formation of primordial follicles by suppressing pregranulosa cell proliferation and downregulating the expression of genes related to the cell cycle, including cyclin D2, CDK4 and CDK6 [ 30 ]. During folliculogenesis, more than 99 % of ovarian follicles undergo atresia, and the roles of miRNAs in regulating follicle development and atresia were recently elucidated.…”
Section: Mirnas and Ovarian Functionmentioning
confidence: 99%
“…Regardless of mammalian species, miR-143 is among the most predominate miRNAs expressed in the ovary (70). Dysregulated miR-143, in mouse models, has been implicated in obesity-associated insulin resistance (71), in the formation of primordial follicles (72) and progesterone release (73).…”
Section: Discussionmentioning
confidence: 99%